COMBINED PREPARATIONS IN THE THERAPY OF BRONCHIAL ASTHMA IN CHILDREN - E.A. Vishneva; R.M. Torshkhoeva; Yu.G. Levina; A.A. Alekseeva (Union of pediatricians of Russia, 2010)
The article describes in detail the therapy for bronchial asthma with combined preparations. The key advantage of combining longacting inhalant corticosteroids and β2-agonists in one inhalant is the simultaneous delivery of effective inhalant preparations to the lungs. Such approach increases the commitment of patients to the prescribed therapy thus making it easier to achieve compliance. Key words: bronchial asthma, control, combined preparations. (Pediatric Pharmacology. - 2010; 7(1):68-71)